2019
DOI: 10.2147/copd.s232339
|View full text |Cite
|
Sign up to set email alerts
|

<p>Not All COPD Patients Benefit from Prophylactic Noninvasive Ventilation After Scheduled Extubation: An Exploratory Study</p>

Abstract: BackgroundProphylactic noninvasive ventilation (NIV) after scheduled extubation can benefit patients with chronic respiratory disorders, among which chronic obstructive pulmonary disease (COPD) is a significant example. However, it is not known whether all COPD patients benefit from prophylactic NIV.MethodsWe performed a post hoc analysis of prospectively collected data. COPD patients who successfully completed a spontaneous breathing trial were enrolled. In the prophylactic NIV group, NIV was applied immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Sensitivity analysis also indicated that NIV remains the most effective method in nonhypercapnic critically ill medical patients. However, an observational study by Gong et al [54] found a conflicting result that prophylactic NIV could not reduce re-intubation or hospital mortality in COPD patients with PaCO 2 < 45 mmHg. It is noteworthy that in our NMA, most trials that enrolled nonhypercapnic patients had a high risk of extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis also indicated that NIV remains the most effective method in nonhypercapnic critically ill medical patients. However, an observational study by Gong et al [54] found a conflicting result that prophylactic NIV could not reduce re-intubation or hospital mortality in COPD patients with PaCO 2 < 45 mmHg. It is noteworthy that in our NMA, most trials that enrolled nonhypercapnic patients had a high risk of extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a risk factor for reintubation after extubation and predisposes patients to hypercapnia during SBT [46]. Thus, NPPV is more effective than COT for patients with hypercapnia after extubation [50], which possibly led to differences in results between our study and that of Zhou et al Furthermore, including trials with many COPD patients potentially increases the patient heterogeneity. Therefore, we excluded trials where COPD patients accounted for >50% of the study population.…”
Section: Discussionmentioning
confidence: 63%
“…COPD is a risk factor for reintubation after extubation and predisposes patients to hypercapnia during SBT [ 46 ]. Thus, NPPV is more effective than COT for patients with hypercapnia after extubation [ 50 ], which possibly led to differences in results between our study and that of Zhou et al Furthermore, including trials with many patients with COPD potentially increased the patient heterogeneity. Therefore, we excluded trials where COPD patients accounted for > 50% of the study population.…”
Section: Discussionmentioning
confidence: 74%